Skogstillväxten ca 20 år efter plantering på Flakmossen : dikningens och gödslingens betydelse vid beskogning på en avslutad torvtäkt i Värmland - Lehto, Björn (SLU/Dept. of Silviculture, 2005)
This study was performed in an afforestation experiment established 1982 on an abandoned peat harvesting area, Flakmossen, in the province of Värmland, SW Sweden. The experimen-tal design include planting with Scots pine (Pinus sylvestris), in combination with various drainage intensities (20, 30, and 40 m between ditches), and fertilizer doses 0, 100, and 200 g PK per seedling applied at the date of planting.